PTU-019 Methadone use is associated with the development of common bile duct dilatation among patients with hepatitis C: results of a retrospective cohort study. (28th May 2012) - Ahmed, A; Stanley, A; Forrest, E; Gillespie, R; Neilson, M; Barclay, S
Abstract : Introduction: The synthetic opioid Methadone is widely used in the treatment of opioid dependence. Opioids are known to induce spasm of the sphincter of Oddi, increase common bile duct (CBD) pressures and induce bile duct dilatation. A prior study has shown methadone use to be associated with asymptomatic CBD dilatation among patients with viral hepatitis. We aimed to examine the prevalence of CBD dilatation among methadone users with hepatitis C (HCV) at first attendance and subsequent liver clinic follow-up, in comparison with a control group. Methods: Patients with chronic HCV attending our institution between 2003 and 2010 were identified from the Scottish HCV Database. Age, gender, methadone use, and CBD dilatation (≥8 mm) identified on initial and follow-up abdominal ultrasound scan (AUS) were recorded. Statistical analysis was performed using SPSS to compare methadone users, vs a control group not on methadone. Results: 618 patients were identified, 316 (51.1%) on methadone and 302 (48.9%) not. Mean age (42.3 vs 48.5, p=0.99) and gender (71.5% male vs 69.2%, p=0.53) were similar in the methadone group vs controls. CBD dilatation on initial AUS was significantly higher among the methadone group (47/316 (14.9%) vs 18/302 (6%), p=0.0003). Post cholecystectomy CBD dilatation was uncommon (4/47 (8.5%) vs 3/18 (16.6%), p=0.38). Of those with a normal initial CBD, 111/269 (41.3%) methadone patients and 115/284 (40.5%) controls had an interval scan. Over similar durations of follow-up (38.1 months vs 45 months controls, p=0.53), methadone use was associated with increased de-novo CBD dilatation (15/111 (13.5%) vs 6/115 (5.2%), p=0.03). Rates of subsequent biliary investigation (MRCP/ERCP) were low (12/62 (19.3%) and 7/24 (29.2%). An obstructive cause of biliary dilatation was infrequently found among methadone receiving patients and controls (1/12 (8.3%) vs 1/7 (14.3%), p=0.49). No obstructive biliary pathology was found among patients with normal alkaline phosphatase (ALP) in either group. Conclusion: Our study confirms the association between methadone use and CBD dilatation among patients referred for assessment of HCV. For the first time we have demonstrated an increased rate of new CBD dilatation among methadone users on longitudinal follow-up. Given that one in five patients on methadone demonstrated CBD dilatation during initial assessment or follow-up, with no alternate cause identified among those with a normal ALP, further investigation of these patients may not be necessary. Further work is required to establish and validate algorithms identifying those patients receiving methadone with CBD dilatation in whom further investigation can be safely omitted. Competing interests: None declared.